(untitled) (JURNAL ADMINISTRASI PUBLIK, 2015)
This study aimed to determine the development of policy implementation discipline government officials / civil servants in the Department of Population and Civil Registration of North Halmahera, and the impact of the implementation of that policy to increase discipline of local government officials. This study used qualitative methods. The informants are all local government officials in the Department of Population and Civil Registration of North Halmahera as many as 13 people. Instruments in this study is the researchers themselves, while collecting data using interview techniques. Data was analyzed using qualitative analysis techniques interactive Model of miles hubernann The results of the study provide conclusions: (1) the implementation of civil service discipline policy guidance to local government officials have been done with good views of several aspects: the high commitment of the leadership to implement this policy, any communication or sosialilisasi effective civil service disciplinary rules to employees, concrete efforts to increase the awareness of employees to carry out the provisions of civil service discipline and creating a culture of discipline, and their enforcement consistently disciplined for violation of obligations and prohibitions. (2) Implementation of policies fostering civil discipline has a positive impact on improving the discipline of local government officials have seen improved adherence and compliance officers against liability provisions and restrictions that apply to civil servants. Based on the conclusions of the research results presented suggestions: (1) the implementation of development policies aperture discipline local government should be directed at increasing awareness that will happen purely on self-discipline each apparatus; (2) Implementation of policy guidance apparatus discipline will provide a more significant positive impact on the improvement of discipline only if accompanied by an increase in the welfare of the key aparatur.Kata: coaching discipline policy apparatus / PNS